2022
DOI: 10.3390/polym14204312
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrical Signal of Non-Poled 3D Printed Zinc Oxide-Polyvinylidene Fluoride Nanocomposites

Abstract: Polyvinylidene fluoride (PVDF) presents highly useful piezo and pyro electric properties but they are predicated upon the processing methods and the ensuing volume fraction of the β-phase. Production of PVDF with higher β-phase content for additive manufacturing (AM) is particularly desirable because it can enable the creation of custom parts with enhanced properties. Necessary steps from compounding to the testing of a 3D printed piezo sensitive sensor are presented in this paper. AM process variables and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Significant decrease in Δ H m was observed at 10 wt % loadings of both SiNPs and F-SiNPs, indicating that the particles contributed to the alteration of the crystalline domains upon solvent processing. This was most affected by the F-SiNPs as a result of the better interdigitating of the fluoroalkyl chains with the amorphous domains of the PVDF polymer chains, which has also been observed similarly with other metal oxide modifiers in PVDF [ 15 ]. The modest increase in the Δ H m of the 1wt % F-SiNP/PVDF (44.2 J/g) composite compared with the virgin-processed PVDF (39.0 J/g) suggests, at low loading, the F-SiNPs may induce the nucleation of PVDF crystalline domain formation.…”
Section: Resultsmentioning
confidence: 67%
“…Significant decrease in Δ H m was observed at 10 wt % loadings of both SiNPs and F-SiNPs, indicating that the particles contributed to the alteration of the crystalline domains upon solvent processing. This was most affected by the F-SiNPs as a result of the better interdigitating of the fluoroalkyl chains with the amorphous domains of the PVDF polymer chains, which has also been observed similarly with other metal oxide modifiers in PVDF [ 15 ]. The modest increase in the Δ H m of the 1wt % F-SiNP/PVDF (44.2 J/g) composite compared with the virgin-processed PVDF (39.0 J/g) suggests, at low loading, the F-SiNPs may induce the nucleation of PVDF crystalline domain formation.…”
Section: Resultsmentioning
confidence: 67%
“… 44 Recently, Joshi et al reported that the addition of zinc oxide nanofiller increased the percent β-phase in MEX printed PVDF. 45 These studies indicate the potential of PVDF/POSS blends for use in high throughput additive manufacturing processes like MEX printing. However, there is a need for further understanding of the relationships between rheology, processing, crystallization, and properties.…”
Section: Introductionmentioning
confidence: 88%
“…In a separate work, Martins et al reported a reduction in the crystallization rate and a small increase in the interlamellar amorphous phase in PVDF blends with 5 wt % POSS . Recently, Joshi et al reported that the addition of zinc oxide nanofiller increased the percent β-phase in MEX printed PVDF . These studies indicate the potential of PVDF/POSS blends for use in high throughput additive manufacturing processes like MEX printing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, β Phase crystallization can be enhanced by adding nano fillers such as carbon materials [ 38 , 80 , 81 ], metal nanoparticles/nanofibers, [ 72 , 82 ] semiconductive ceramic [ 83 , 84 ], and other polymers [ 85 , 86 ]. The nanofibers of PVDF copolymers and their nanocomposites have been successfully prepared into oriented PVDF nanofibers, which were used as functional layers of piezoelectric sensors and piezoresistive sensors with excellent performance.…”
Section: Polymersmentioning
confidence: 99%